Selenium a little known element with an important biological role - Cañari Chumpitaz, Cristhian (2011)
Selenium is an essential micronutrient present in various organisms including human beings. This element may be found in different organic and inorganic metabolites, and selenocysteine (Sec) is the most important. The insertion of Sec in selenoproteins uses a unique mechanism that involves the recoding of the UGA codon. This process requires new RNA fragments like the selenocysteine insertion sequence (SECIS) in the mRNA. The function of many selenoproteins is not known completely; however, some of them are involved in intracellular redox signaling regulation, redoxhomeostasis and thyroid hormone metabolism. Se deficiency in humans affects human health and results in diseases such as cancer, Keshan disease and hormonal disfunctions.